Globalization and social change people and places in a divided world - Perrons, Diane
Detailed comparative and illuminating case studies from a wide range of countries document and explain how and why different people in different places are affected by and in turn affect these processes. The book concludes that contemporary inequalities are widening, that divisions by social class, ethnicity and gender are in some ways becoming more significant than divisions between nations, suggesting that new systems of governance are necessary for social tranquility in the new millennium.